APPLICATION OF FOREST CANOPY DENSITY (FCD) MODEL FOR THE HOTSPOT MONITORING OF CROWN FIRE IN TEBO, JAMBI PROVINCE - Falensky, Muhammad Attorik; Sulti, Anggieani Laras; Putra, Ranggas Dhuha; Marko, Kuswantoro (UI Scholars Hub, 2020)
Indonesia is one of the owners of the 9th largest forest area in the world. Forest area in Indonesia reaches 884,950 km2 . Tebo Regency is a regency in Jambi Province which has a wide forest area of 628,003 Ha. However, this forest area has been reduced due to the conversion of functions of Industrial Plantation Forests (HTI), oil palm plantations, and forest clearing activities for both settlements and plantations which led to the phenomenon of forest and land fires (karhutla). This study aims to get a better knowledge of crowns of fire potential locations in forest areas using remote sensing technology. Remote sensing data used in this study is from the satellite imagery of Landsat 8 OLI - TIRS in 2019. Remote sensing data is used to produce a Forest Canopy Density (FCD) model that can be overlapped with a hotspot location, so the crown fire potential locations will be explored in the forest area of Tebo Regency, Jambi Province. Identification of hotspot patterns in Forest Areas was analyzed using spatial analysis. The results of this study are useful for the government as the information of the hotspot area as the cause of fires in the Forest Region of Tebo Regency Jambi Province.